Numerical Assessment of the Immersion Process of a Ceramic Foam Filter in a Steel Melt. Issue 2 (20th September 2021) - Asad, Amjad; Lehmann, Henry; Jung, Bernhard; Schwarze, Rüdiger
Abstract : Herein, the immersion process of a ceramic foam filter in a steel melt is investigated by means of numerical simulations, which are mainly based on the volume of fluid approach. The geometry of the used filters is modeled using an artificially generated beam model, which is convolved with a Gaussian kernel. The modeling approach enables the generation of filter geometries with, e.g., pore density and strut thickness similar to real ceramic foam filters. The main scope of the article is to show the effect of the immersion velocity of the filter on the formation of gas bubbles inside the pore cavities of the ceramic filter. Moreover, the influence of the contact angle on the volume fraction of gas bubbles, which remain in the filter, is investigated. For better understanding, the numerical results are underlined using 3D visualization and virtual reality. Abstract : Herein, the immersion process of a ceramic foam filter is investigated. The main aim of the article is to show the effect of the immersion velocity and the contact angle on the bubble entrapment on the filter walls.